PEMIKIRAN IMAM SYAFI’I TENTANG KEDUDUKAN MASLAHAH MURSALAH SEBAGAI SUMBER HUKUM - Aris, Aris (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2013)
This paper studies regarding one aspect of the discussion about the science of motion fikhi beneficiaries mursalah position as a source of law in the view of Imam Shafi'i. The issue is how thinking about the position of Imam Shafi'i maslahah mursalah as a source of law. In the discussion of its principles Fiqhi, one of the sources of law that is often disputed among scholars of usul use is maslahah mursalah. Imam Shafi'i firmly rejected mursalah maslahah use as a source of law to argue that Islamic law has come with all the laws that realize the benefit of all human beings, either through the Koran and Hadith or qiyas manner to the existing case law.